Servant leadership and psychological well-being: A philosophical perspective and the role of religiosity and power distance orientation - Muhammad Azeem Qureshi; Ummi Naiemah Saraih; Muhammad Sufyan Ramish (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
The COVID-19 pandemic has posed a vital challenge to traditional leadership practices. The virtual workplace is changing the way people are accustomed to working. Despite flexibility regarding time and space with the advent of digital technologies, employees face several psychological problems while working remotely. Servant leadership is one of the possible solutions to address this issue, but there is a question mark on servant leadership effectiveness in high power distance cultures. However, the closeness of servant leadership to religious beliefs can make it effective in such cultures. This research addresses the philosophy of servant leadership theory and employs Structural Equation Modeling (SEM) to test a theoretical model to determine how servant leaders can positively impact employees working distantly. This research reveals that servant leadership helps employees cope with occupational and perceived stress and maintains their work-life balance by ensuring their psychological wellbeing. This research also finds that the compatibility of servant leadership with religiosity makes it more effective irrespective of cultural differences.
Keywords: 330; Servant Leadership; Power Distance; Religiosity; Psychological Well-being; Occupational Stress; Perceived Stress; Work-life Balance; Pakistan